2009
DOI: 10.1182/blood-2009-04-218651
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of hematopoietic stem cell collection from mobilized peripheral blood in unrelated volunteers: 12 years of single-center experience in 3928 donors

Abstract: We present results of peripheral blood stem cell (PBSC) mobilization, collection, and follow-up from 3928 consecutive unrelated stem cell donors. Assessments were performed prospectively at baseline, leukapheresis, 1 month, 6 months, and annually after PBSC donation. During follow-up, side effects were recorded by return post questionnaires. The median CD34 ؉ cell counts on day 5 were 67.5/L in male and 51/L in female donors. Bone pain and headache were the most common side effects of recombinant human granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
164
3
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(195 citation statements)
references
References 28 publications
22
164
3
6
Order By: Relevance
“…Long-term increased risks of PBSC donation have not been identified [36,37], but remain of concern, in particular development of haematological malignancy, solid tumours, myelodysplasia, vascular and autoimmune diseases. In the retrospective EBMT study, a follow-up questionnaire revealed that 20 out of 51 000 donors had developed a haematological malignancy between 4 months and 12 years post-donation (15 related donors and 5 not reported) [30].…”
Section: Long-term Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term increased risks of PBSC donation have not been identified [36,37], but remain of concern, in particular development of haematological malignancy, solid tumours, myelodysplasia, vascular and autoimmune diseases. In the retrospective EBMT study, a follow-up questionnaire revealed that 20 out of 51 000 donors had developed a haematological malignancy between 4 months and 12 years post-donation (15 related donors and 5 not reported) [30].…”
Section: Long-term Follow-upmentioning
confidence: 99%
“…In the retrospective EBMT study, a follow-up questionnaire revealed that 20 out of 51 000 donors had developed a haematological malignancy between 4 months and 12 years post-donation (15 related donors and 5 not reported) [30]. The large unrelated donor registries now collect long-term outcome data of donors in a systematic prospective manner [33][34][35][36][37].…”
Section: Long-term Follow-upmentioning
confidence: 99%
“…[16][17][18][19] Current experience suggests that risks seem to be higher for related than for unrelated donors with the caveat of reporting bias and lack of an adequate amount of prospective follow-up data in the related donor setting. [9][10][11]18 These rare SAE/R that occur with estimates of about 1 in 3-5000 for serious and 1 in 10-20 000 for lethal events are still incompletely understood. [9][10][11][16][17][18][19] Hence, there is urgent need for better understanding of short-term SAR and to identify donors at risk.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11]18 These rare SAE/R that occur with estimates of about 1 in 3-5000 for serious and 1 in 10-20 000 for lethal events are still incompletely understood. [9][10][11][16][17][18][19] Hence, there is urgent need for better understanding of short-term SAR and to identify donors at risk. Because of the rarity of the events, progress can only be achieved by large international collaborations that include both unrelated and related donors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation